Visual memory recovery by nender in young athletes with a sport-related concussion (SRC) - Yoo, H. (The Sport Journal, 2023)
Objective This study aimed to determine 1) whether there are gender differences in the post-concussion (PC 1-3) recovery process in visual memory after a concussion, and 2) whether there is interaction between two gender groups and the number of concussions.